Kepemimpinan Tradisional Masyarakat Minangkabau pada Masa Pendudukan Jepang - Fatimah, Siti (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTARCT As an ethnic group Minangkabau people was influenced by many conditions developed around them, like scio-cultural, value system they had, beliefs and religious, and status and roles they played. Based on those conditions, Minangkabau people has been well-known with their unique community structure and leadership pattern in the past. This condition had been running in harmony until the coming of Japanese colonialism in 1943. This pattern of leadership had been changed and tended to be disfunctional. In their colonialism era, Japanese tried to use the Tungku Tigo Sajarangan (the pattern of Minangkabau traditional leadership) as a tool for maintaining their power over Minangkabau colony. Kata Kunci: Kepemimpinan, pola dan sistem kepemimpinan, kepemimpinan tradisional, Minangkabau,